Optimalisasi Model Project Based Learning terhadap Motivasi Belajar Mahasiswa Calon Guru Fisika Di Era New Normal - Aji Saputra; Saprudin Saprudin; Fatma Hamid; Nurdin Abdul Rahman (Pendidikan Fisika Universitas Nurul Huda, 2023)
Education is one of the sectors that has been affected by the Covid-19 pandemic. Currently we have entered the